The identity of Psilochironomus Sublette, 1966 (Chironomidae, Chironominae, Pseudochironomini) - Andersen, Trond; Sanz-Laparra, Annui Malla; Giłka, Wojciech (Zootaxa, 2024)
Chironomus fumeus Walley in Curran, 1934 was described based on a single male from British Guyana. When reviewing the type specimens of Chironomidae (Diptera) in the American Museum of Natural History, Sublette erected the monotypic genus Psilochironomus Sublette, 1966 based on the species. Subsequently, Sæther included the genus when he suggested the new tribe Pseudochironomini Sæther, 1977. However, the type specimen’s hypopygium has been missing since before Sublette’s examination; thus, Spies & Reiss in 1996 considered both C. fumeus and Psilochironomus to be nomina dubia. Below we redescribe C. fumeus based on four males collected by E.J. Fittkau in Pará State in northern Brazil and give an emended diagnosis for Psilochironomus. An updated key to the genera of Pseudochironomini is included.